Effects of Gamma Ray Irradiation to Induce Genetic Variability of Teak Planlets (Tectona grandis Linn. F.) - Supriyanto; Arum Sekar Wulandari; Ahmad Parlaongan (Talenta Publisher, 2022)
Teak planlets (Tectona grandis) of Salomon clones were irradiated by gamma rays to induce genetic variability for growth improvement. The objectives of this research were to analyze the radiosensitivity of T. grandis Salomon clones by gamma ray irradiation and to analyze the genetic variations using Random Amplified Polymorphic Deoxyribonucleic Acid (RAPD). For those purposes, teak planlets were irradiated using gamma rays at 5 different dosages, those were 0 Gy, 10 Gy, 20 Gy, 30 Gy, and 40 Gy. Lethal doses50 (LD50) and reduced doses50 (RD50) were obtained using Curve-fit Analysis. Furthermore, the irradiated planlets were subcultured on medium MS + 0.1 kinetin (M1V0) the surviving M1V0 plantlets were multiplied to MS + 0.1 kinetin, so it is obtained the M1V1 generation. Genetic variation of the mutant was molecularly analyzed using RAPD methods and the variability was calculated using Analysis of Molecular Variance (AMOVA). Results of this research showed that lethal doses50 (LD50) and reduced doses50 (RD50) values were obtained at 24.5 Gy and 7.85 Gy, respectively. It includes genomes of small size and a small number of genomes. The genetic variation of mutant individuals in among and within the treatment of gamma irradiation was 16% and 84% according to AMOVA. It means that the dominant effect of genetic material caused genetic variation in mutant M1V1 generations. This dominance of genetic material could be caused by the response combination of tissue culture treatment and genetic factors that had the potency to be used as materials to select desired clones in the next stage.